Tin and Lead Alkoxides of Ethylene Glycol and Glycerol and their Decomposition to Oxide Materials - Teichert, Johannes; Block, Theresa; Poettgen, Rainer; Doert, Thomas; Ruck, Michael (European Journal of Inorganic Chemistry, 2019)
A comprehensive investigation of the formation of tin and lead alkoxides with the polyalcohols ethylene glycol (C2H6O2, EG) and glycerol (C3H8O3) was conducted. Starting from tin(II) and lead(II) precursors, five alkoxides with either double- or triple-deprotonated alcohol ligands were obtained. Four of them were structurally characterized by single-crystal and one by powder X-ray diffraction. The ethylene glycolates of tin(II) and lead(II), Sn(C2H4O2) and Pb(C2H4O2), show polymorphism. α- and β-Sn(C2H4O2) can be synthesized selectively by applying different reaction times. α- and β-Pb(C2H4O2), as well as Pb4(C2H4O2)4(C2H6O2), were obtained by altering the amount of NaOH and/or water used in the synthesis. With glycerol, mixed-valent tin(II,IV) glycerolate Sn5(C3H5O3)4 and lead(II) glycerolate Pb(C3H6O3) crystallized. Except for Pb(C2H4O2), the obtained alkoxides are stable at ambient conditions for at least several months. The tin alkoxides were thermally decomposed in air to SnO2. A small amount of tin(II) in a SnO2 sample obtained at a low decomposition temperature was revealed by 119Sn Mössbauer spectroscopy. At the highest decomposition temperature of 800 °C, only tin(IV) could be detected. The morphology of the alkoxide material is retained upon decomposition; however, the produced SnO2 consists of nanosized crystalline domains. The thermal decomposition of the lead(II) alkoxides in air yielded PbO particles with a significantly changed morphology.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Lead; Metal alkoxides; Mössbauer spectroscopy; Polyol process; Tin